Design of Multilateral Wells for the Conditions of Guajira Offshore Basin in the Colombian Caribbean Sea (2022)
This article proposes the design of a multilateral well on the Tayrona area conditions located in the Guajira Offshore basin that belongs to the Colombian Caribbean. This zone has a strategic importance for Colombia, because is where the Orca-1 well was drilled, integrating a substantial gas reservoir detection in 2014, which is a project with great development potential, that can help meet the energy needs of the country, where Ecopetrol, Petrobras, and Repsol are contributing. Reviewed to know about the technique of drilling multilateral wells, perform an analysis of the conventional and modern existing alternatives and both the environmental and operational variables influencing the drilling of this kind of offshore wells. In addition, a research study of environmental and geological conditions of the interest area, the Colombian Guajira offshore, was carried out to determine the feasibility of the application of this technology. The design of the multilateral well UIS-OFF-MO1 was proposed, with two opposite branches to increase production in the reservoir in which Orca-1 well is situated, to increase the drainage area and contact an area of the reservoir, which is separated by a normal no-flow fault. © 2022 Academic Publishing House. All rights reserved.